2021
DOI: 10.1186/s13031-021-00373-6
|View full text |Cite
|
Sign up to set email alerts
|

Tools for measuring gender equality and women’s empowerment (GEWE) indicators in humanitarian settings

Abstract: Background Effective measurement of Gender Equality and Women’s Empowerment (GEWE) is challenging in low and middle-income countries (LMICs), and even more so in humanitarian settings. Conflict, natural disasters, and epidemics may increase gender inequities, but also present an opportunity to address them. This scoping review describes and identifies gaps in the measurement tools, methods, and indicators used to measure GEWE in humanitarian settings, and presents a dashboard that can be used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Other studies have reported that social norms in some societies and fear of social stigma are one of the barriers to accessing health services after sexual violence, requiring to be changed before the occurrence of disasters ( 67 - 69 ), which is in line with the present study. The expectations of men in society can lead them to believe that they can abuse women and justify their actions; therefore, changing the norms is effective in reducing the rate of sexual violence; to this end, it is necessary to change the norms before disasters ( 70 ). Another important measure for the proper management of sexual violence is the creation of information circulation systems, and it is necessary to take technical measures to establish a system for collecting information ( 71 ), which is also consistent with the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported that social norms in some societies and fear of social stigma are one of the barriers to accessing health services after sexual violence, requiring to be changed before the occurrence of disasters ( 67 - 69 ), which is in line with the present study. The expectations of men in society can lead them to believe that they can abuse women and justify their actions; therefore, changing the norms is effective in reducing the rate of sexual violence; to this end, it is necessary to change the norms before disasters ( 70 ). Another important measure for the proper management of sexual violence is the creation of information circulation systems, and it is necessary to take technical measures to establish a system for collecting information ( 71 ), which is also consistent with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the results of the present study. Given that sexual violence is taboo in many societies, reporting is an important challenge in this regard, and defining the reporting process based on the cultural sensitivities of that society can be a good solution ( 70 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 2) Relational empowerment refers to the freedom of making decisions, free mobility, social circles, and response to haphazard situations individually or collectively. (3) Societal aspect denotes women's ratios opting for microfinance and rations of women successfully leading the microfinance firms (Goulart, Purewal, Nakhuda, Giancola, Kortenaar & Bassani, 2021;Lee et al, 2021). This model has built its foundation on ecological system theory (Bronfenbrenner, 1994) which implies that individuals starting from their childhood become a part of different environments that form their personalities and experiences.…”
Section: Underpinning Theorymentioning
confidence: 99%
“…While the identification and prioritization of the necessary references are critical to the development of the scoping report, an equally important aspect is the dissemination and exploration of the information contained within each reference. A few papers in recent years have utilized some visualization tools in health science scoping reports, such as Chishtie et al ( 2020 ), Goulart et al ( 2021 ), and Jornod et al ( 2021 ), to visualize health outcome information. While these tools are helpful, we chose to use other tools that were more fit‐for‐purpose to project needs.…”
Section: Structured Approach To Search Screen Select Categorize and C...mentioning
confidence: 99%